Protein-carbohydrate-lipid complex isolated from the cell envelopes of Chlamydia psittaci in alkaline buffer and ethylenediaminetetraacetate. - Narita, T (1976)
Exposure of isolated cell envelopes from purified infectious elementary (EB) of Chlamydia psittaci to sodium carbonate-bicarbonate buffer at pH 10 plus ethylenediaminetetraacetate (EDTA) results in partial solubilization of the total protein. The released materials represent 20% of the dry weight, 16% of the total protein, 40% of the total carbohydrate, and 9% of the total lipid of the cell envelopes. Sucrose density gradient centrifugation, and Sephadex G-200, Sepharose 4B, or diethylaminoethyl-cellulose column chromatography, reveal a protein-carbohydrate-lipid complex of several hundred thousand molecular weight that contains 50% protein. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the isolated EB cell envelopes reveals two major protein bands, A and B, with estimated molecular masses of approximately 85,000 and 53,000, respectively, both of which also stain for the presence of carbohydrate and lipid. Gel electrophoresis of the protein-carbohydrate-lipid complex reveals two protein bands, C and D, with estimated molecular weights of approximately 17,000 and 13,000, respectively, which contain lipid and a small amount of carbohydrate; bands A and B are not present in the complex. Gel electrophoresis of the cell envelope residues after extraction of the complex with alkali and EDTA shows a single main band, corresponding to the position of band B, which contains protein, carbohydrate, and lipid; band A is completely missing. B and A is believed to be a component of the complex, which is split into two subunits on alkali solubilization.